2020
DOI: 10.3389/fcell.2020.00750
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Signaling Interactions and Transport at the Osteochondral Interface: A Review

Abstract: Articular joints are comprised of different tissues, including cartilage and bone, with distinctive structural and mechanical properties. Joint homeostasis depends on mechanical and biological integrity of these components and signaling exchanges between them. Chondrocytes and osteocytes actively sense, integrate, and convert mechanical forces into biochemical signals in cartilage and bone, respectively. The osteochondral interface between the bone and cartilage allows these tissues to communicate with each ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 92 publications
0
20
0
Order By: Relevance
“…Although OA has long been viewed as a primary disorder of articular cartilage, subchondral bone is attracting increasing attention [39]. The pathology at the cellular level of the chondrocyte and the biochemistry within the knee joint have been discussed in extensive detail elsewhere [12,40,41]. In this section, we present an overview of the key pathological features involved in the osteochondral unit.…”
Section: Pathogenetic Profilesmentioning
confidence: 99%
“…Although OA has long been viewed as a primary disorder of articular cartilage, subchondral bone is attracting increasing attention [39]. The pathology at the cellular level of the chondrocyte and the biochemistry within the knee joint have been discussed in extensive detail elsewhere [12,40,41]. In this section, we present an overview of the key pathological features involved in the osteochondral unit.…”
Section: Pathogenetic Profilesmentioning
confidence: 99%
“… 2015 ; Oliveira Silva et al. 2020 ). We previously demonstrated that distinct changes occurred with the progression of osteoarthritis (OA) (Fan et al.…”
Section: Introductionmentioning
confidence: 99%
“…This hyaline cartilage is both avascular and aneuronal. It is made of cells called chondrocytes that synthetize their own surrounding extracellular matrix (ECM) [ 1 , 2 ]. The mechanical properties of articular cartilage depend on its ECM and allow joint surfaces to resist wear [ 1 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%